Fatores que influenciam a confiabilidade do planejamento em obras de habitação de interesse social com ênfase na utilização de sistemas construtivos industrializados - Luciana de Castro Patricio Pimenta (2022)
In recent decades, the growth of competition and supply of services in civil construction in Brazil has made it necessary to use an increasingly specialized workforce and better management of processes, increasing the importance of planning and technological innovations for the execution of projects with greater productivity and quality. In housing projects of social interest, the assertiveness of their planning is especially important, as the profit margins of companies are increasingly smaller and any variation in the cost structure impacts profitability, or even the viability of the enterprise. This present study aimed to identify the factors that influence the reliability of planning in social housing projects, with emphasis on the use of industrialized systems. As a research method, an exploratory case study was used in two construction companies and three projects with different industrialized construction systems: prefabricated structure and fences, cast-in-place concrete wall and structural masonry with concrete blocks. The analyzes were carried out within the scope of each project and the information obtained in the different projects was compared. The results indicate that the more industrialization characteristics the construction system presents, the greater the reliability of its planning. In addition, it was observed that the application of some Design for Manufacture and Assembly (DFMA) guidelines in construction processes can impact the reliability of the planning.